Genetics of the human Y chromosome and its association with male infertility - Stacy Colaco; Deepak Modi (BMC, 2018)
Abstract The human Y chromosome harbors genes that are responsible for testis development and also for initiation and maintenance of spermatogenesis in adulthood. The long arm of the Y chromosome (Yq) contains many ampliconic and palindromic sequences making it predisposed to self-recombination during spermatogenesis and hence susceptible to intra-chromosomal deletions. Such deletions lead to copy number variation in genes of the Y chromosome resulting in male infertility. Three common Yq deletions that recur in infertile males are termed as AZF (Azoospermia Factor) microdeletions viz. AZFa, AZFb and AZFc. As estimated from data of nearly 40,000 Y chromosomes, the global prevalence of Yq microdeletions is 7.5% in infertile males; however the European infertile men are less susceptible to Yq microdeletions, the highest prevalence is in Americans and East Asian infertile men. In addition, partial deletions of the AZFc locus have been associated with infertility but the effect seems to be ethnicity dependent. Analysis of > 17,000 Y chromosomes from fertile and infertile men has revealed an association of gr/gr deletion with male infertility in Caucasians and Mongolian men, while the b2/b3 deletion is associated with male infertility in African and Dravidian men. Clinically, the screening for Yq microdeletions would aid the clinician in determining the cause of male infertility and decide a rational management strategy for the patient. As these deletions are transmitted to 100% of male offspring born through assisted reproduction, testing of Yq deletions will allow the couples to make an informed choice regarding the perpetuation of male infertility in future generations. With the emerging data on association of Yq deletions with testicular cancers and neuropsychiatric conditions long term follow-up data is urgently needed for infertile men harboring Yq deletions. If found so, the information will change the current the perspective of androgenetics from infertility and might have broad implication in men health.